Being a student, becoming a teacher: The wellbeing of pre-service language teachers in Austria and the UK. (October 2021) - Mairitsch, Astrid; Babic, Sonja; Mercer, Sarah; Sulis, Giulia; Jin, Jun; King, Jim
Abstract: This paper reports on a study designed to investigate the wellbeing of 14 pre-service language teachers from Austria and the UK. Data were generated through in-depth semi-structured interviews which were analysed following principles of Grounded Theory (Charmaz, 2006). The data were compared across the two settings and the analysis revealed a number of individual but also systemic ecological factors that play a role in the pre-service teachers' wellbeing. These factors include time management, work-life balance, relationships, finding purpose and meaning, the structure of study programs, as well as the status of teaching and the specific language in each respective society. Highlights: Data generated through 14 in-depth semi-structured interviews. Study takes an ecological perspective with comparative design. Data analysed following principles of Grounded Theory (Charmaz, 2006). Results: Individual and systemic factors appear to influence pre-service language teacher wellbeing. Other factors include work-life balance, relationships, structure of study programs, and the status of language teaching.